2017
DOI: 10.1002/slct.201700939
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Molecular Interaction in Solutions by Chemometric Resolution of Near−Infrared Spectra

Abstract: Interactions in aqueous solutions have been extensively studied using spectroscopic techniques. Due to the complexity of the spectra, however, it is difficult to obtain the spectral components showing the interactions in the system. In this study, a chemometric method for resolution of overlapping analytical signals was proposed based on the rotation of the loadings in principal component analysis (PCA). The method was applied to calculating the spectra of ethanol and water from the near infrared (NIR) spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…In IC2, IC3, and IC4, one main peak is obtained for each IC, which is located at 7072, 6968, and 6826 cm À1 , respectively. According to the previous works, [19][20][21]26,31,[33][34][35][36][37]53 the peaks correspond to the absorption of n 1 þ n 3 of the differently hydrogen-bonded OH, i.e., the free OH (S 0 ), OH with one hydrogen bond (S 1 ) and OH with two hydrogen bonds (S 2 ), respectively. The positive peaks around 7200 cm À1 in IC4 may also be the information of water vapor.…”
Section: Structural Changes Of Water Induced By D 5 and Kmentioning
confidence: 87%
See 1 more Smart Citation
“…In IC2, IC3, and IC4, one main peak is obtained for each IC, which is located at 7072, 6968, and 6826 cm À1 , respectively. According to the previous works, [19][20][21]26,31,[33][34][35][36][37]53 the peaks correspond to the absorption of n 1 þ n 3 of the differently hydrogen-bonded OH, i.e., the free OH (S 0 ), OH with one hydrogen bond (S 1 ) and OH with two hydrogen bonds (S 2 ), respectively. The positive peaks around 7200 cm À1 in IC4 may also be the information of water vapor.…”
Section: Structural Changes Of Water Induced By D 5 and Kmentioning
confidence: 87%
“…33 Furthermore, the methods for resolving the spectral components of different water species and the pure component spectra from the measured spectra of aqueous solution were developed to study the molecular interaction in solutions and the effect of the solute on water structure. 34,35 In these studies, the feasibility for analyzing the molecular interactions using temperature-dependent NIR spectra was proved and water can be a probe for the analysis. Similar works were also reported such as the early diagnosis of amyloidosis 36 and estrus detection of female giant panda 37 using NIR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Through the variation of the spectra with the concentration, it was revealed that ethanol promotes the formation of water clusters. To obtain more spectral information of the interactions of water and ethanol, a new method was proposed based on the rotation of the loadings in principal component analysis (PCA) [42]. The calculated spectra were found to be more reliable to reflect the structures in the mixture, from which the spectral features of different water species (S 0 -S 4 ), ethanol clusters, and the interaction of OH and CH groups were observed.…”
Section: Interaction Of Water and Solutesmentioning
confidence: 99%
“…The influence of temperature on the structure of Ara h1 was characterized by an aquagram. The characteristic absorption bands of the Ara h1 aqueous solution during temperature change were shown in Table 2 (32)(33)(34)(35)(36)(37)(38)(39). The aquagram with the 12 WAMACS was shown in Figure 8.…”
Section: Ara H1 Aquagram Analysismentioning
confidence: 99%